Clinical Crown Length, Width and the Width/Length Ratio of the Maxillary Central Incisor Among Patients Reporting to a Tertiary Care Center in Nepal - Bhochhibhoya, A; Shrestha, R; Guragain, M; Sharma, R; Joshi, KR (Journal of Nepalese Prosthodontic Society, 2022)
Introduction: The most important aspect of dental and facial esthetics is the display of anterior teeth. It becomes a primary consideration to restore the correct size and proportion of anterior teeth for patients seeking prosthodontic treatment. There is tremendous influence of geographic location, race, ethnic background, gender in determining the size and proportion of anterior teeth. There is paucity of data regarding the width, length and width/length ration of central incisors in Nepalese population.Methods: An Observational, descriptive study was conducted in patients visiting T.U. Dental Teaching Hospital. Maxillary impression was made in alginate impression material and poured in dental stone. A digital caliper was used for the measurements, with a precision of 0.01 mm. The maximum mesiodistal width and the maximum crown length of the maxillary central incisors was recorded for each tooth. These data was tabulated and the width/length ratio was calculated. Data was analyzed using Statistical Package for Social Science Version 17 (SPSS Ver. 17) and descriptive statistics was calculated.Results: A total of 127 participants were included in the study of which 64 (50.39%) were males and 63 (49.61%) were females. The mean width/length ratio for right and left central incisors are 0.89 and 0.86 respectively for males and 0.89 on both the sides for females. In case of right central incisors, males had higher mean crown width and length than female and these differences were found to be statistically significant. In case of left central incisor, there was a statistically significant difference in mean crown length between male and female, males having higher length score than female.Conclusion: Males had higher mean crown width and length than female and these differences were found to be statistically significant. The width/length ration for central incisor ranged from 0.86 to 0.89. Knowledge about the size and proportion of upper anterior teeth allows dental rehabilitation taking into consideration the local parameters of a population.